Acute extracorporeal shockwave lithotripsy for ureteric stones – 7‐years' experience from a busy district general hospital. (27th June 2022) - Young, Matthew J.; Pang, Karl H.; Elmussarah, Muhammad; Hughes, Paul F.; Browning, Anthony J.; Symons, Stephanie J.
Abstract : Objectives: To demonstrate the efficacy and cost‐effectiveness of acute extracorporeal shockwave lithotripsy (ESWL) for ureteric stones we present our experience of ESWL in 530 ureteric stone cases, in the largest UK series we are aware of to date. ESWL is underutilised in ureteric stone management. The Getting It Right First Time (GIRFT) report showed just four units nationally treated >10% of acute ureteric stones with ESWL. Despite guideline recommendations as a first‐line treatment option, few large volume studies have been published. Patients and Methods: Retrospective review of prospectively collected data between December 2012 and February 2020 was performed. Data relating to patient demographics, stone characteristics, skin‐to‐stone distance, and treatment failure were collected. Cost analysis was conducted by the Trust's surgical financial manager. Multivariable analyses were performed to assess for predictors of ESWL success. Results: A success rate of 68% (95% confidence interval 64%–72%) at 6 weeks was observed ( n = 530). The median (interquartile range) number of treatment sessions was 2 (1, 2). Stone diameter was observed to be a predictor of ESWL success. The small number of stones treated of >13 mm or >1250 HU had an 50% chance of successful treatment. Acute ureteric ESWL was less costly than acute ureterorenoscopy, consistent with findings from previous NHS studies. Conclusion: Acute ESWL is a safe, reliable, and financially viable treatment option for a wider spectrum of patients than reflected in international guidelines based on our large, heterogenous series. In the coronavirus disease 2019 (COVID‐19) era, with theatre access reduced and concerns over aerosol generating procedures, acute ESWL remains an attractive first‐line treatment option.